Supplemental measles vaccine antibody response among HIV-infected and -uninfected children in Malawi after 1- and 2-dose primary measles vaccination schedules - Fowlkes, Ashley L. (Vaccine, 2016)
BACKGROUND: The long-term antibody response to measles vaccine (MV) administered at age 6 months with or without subsequent doses is not well documented. METHODS: Measles serum antibody responses were evaluated after a supplemental dose of measles vaccine (sMV) administered at a median age of 20 months among Malawian children who had previously received 2 doses of measles vaccine (MV) at ages 6 and 9 months (HIV-infected and random sample of HIV-uninfected) or 1 dose at age 9 months (random sample of HIV-uninfected). We compared measles antibody seropositivity between groups by enzyme linked immunoassay and seroprotection by plaque reduction neutralization geometric mean concentrations. RESULTS: Of 1756 children enrolled, 887 (50.5%) received a sMV dose following MV at 9 months of age and had specimens available after sMV receipt, including 401 HIV-uninfected children who received one MV dose at 9 months, 464 HIV-uninfected and 22 HIV-infected children who received two doses of MV at ages 6 and 9 months. Among HIV-uninfected children, protective levels of antibody were found post sMV in 90–99% through ages 24–36 months and were not affected by MV schedule. Geometric mean concentration levels of measles antibody were significantly increased post-sMV among those HIV-uninfected children previously non-responsive to vaccination. Among HIV-infected children, the proportion seroprotected increased initially but by 9 months post-sMV was no higher than pre-sMV. CONCLUSIONS: Our findings support early 2-dose MV to provide measles immunity for young infants without risk of interference with antibody responses to subsequent MV doses administered as part of SIAs.